Environmental Ergonomic Design Slope Limits to Prevent Accidents - Gempur Santoso (International Journal of Scientific Multidisciplinary Research, 2024)
Living on a slope is indeed dangerous, there is a high possibility of landslides, and it can also be a disaster because of the loss of life. This article reveals that settlements on sloping land must pay attention to the ergonomic limits of the slope angle to avoid accidents in the environment. This writing is designed descriptively/expositionally. Data was taken from various literature in the form of opinions from research related to environmental design regarding slope limits for non-stone soil. Conclusion: First, ergonomic limits for settlements can be made on a ground slope of 4 - 8 degrees or a slope of 7% - 15%. Second, living on a slope exceeding the ground angle of 4 - 8 degrees or a slope exceeding 7% - 15% will cause accidents. The causes of accidents living on slopes include: erosion, landslides, the value of the safety factor, which is what determines the soil's ability to accept small compressive and tensile loads and makes the slope increasingly unsafe. Suggestion: It is best to build a house or building not on a slope where the slope angle exceeds 4 - 8 degrees or the slope exceeds 7% - 15% to avoid accidents